EVALUASI USER INTERFACE E-LEARNING UNIVERSITAS JAMBI MENGGUNAKAN SYSTEM USABILITY SCALE - agustin, zeri (JUSS (Jurnal Sains dan Sistem Informasi), 2021)
Abstract In a website, the user interface is very important, because the user interface is where the user interacts with the website. A good user interface of course will greatly facilitate users to get information or services offered on a website. Testing the quality of the Jambi University E-Learning user interface in this study was carried out using the SUS (System Usability Scale) method. This test was carried out by distributing a questionnaire containing ten questions that were already available in the SUS method. After doing the research, the SUS score obtained by E-Learning Jambi University was 73.46. From this score, it is known that the percentile level is above the average, which is 65%. Then, the grade received by Jambi University's E-Learning is B and the Adjective scale is good, which means the Jambi University's E-Learning website has good quality. Furthermore, the level of acceptability is at the level of acceptable or can be accepted and understood by the respondents well. For the NPS score, Jambi University's E-Learning is in the Passive classification, which means that respondents are passive in recommending E-Learning to be used by others. Respondents have not actively invited others to use Jambi University's E-Learning.